Antibacterial screening of syzygium mimicum leaf methanolic extract againt UTI-causing pathogens enterococcus faecalis, staphylococcus saprophyticus, Escherichia coli, and Proteus mirabilis - Bungue, Denisse Trisha A., Libunao, Franchezca Luis A., Narvaez, Patricia Jhoy, Santos, Jahaziel Sarah B., Yu, Hannah Angel A. 4 0 16; 5
ABSTRACT: Urinary Tract Infection is a prevalent bacterial infection worldwide that is common in outpatient or inpatient settings. The increasing antimicrobial resistance poses a significant ongoing problem. Therefore, the discovery of materials with potential antimicrobial properties is crucial to address this threat. This study investigates the phytochemical compounds present on Syzygium mimicum methanolic leaf extract and its antibacterial activity against selected UTI-causing pathogens. Disk diffusion method and broth microdilution method were used to test gram-positive bacteria, Staphylococcus saprophyticus and Enterococcus faecalis, and gram-negative bacteria, Escherichia coli and Proteus mirabilis. The bacteria were treated with Syzygium mimicum methanolic leaf extract and was diluted in 10% Dimethyl Sulfoxide. The mother stock of Syzygium mimicum extract was further diluted into different concentrations, 100%, 75%, 50%, and 25%. The qualitative phytochemical analysis of Syzygium mimicum leaves showed a presence of phytochemical compounds such as phenols, flavonoids, terpenoids, tannins, alkaloids, and saponins. The Syzygium mimicum methanolic leaf extract was active and exhibited the largest zone of inhibition against Staphylococcus saprophyticus and was partially active on Proteus mirabilis and on Enterococcus faecalis. Meanwhile, Syzygium mimicum methanolic leaf extract was inactive in Escherichia coli. In broth microdilution, the Syzygium mimicum extracts exhibited reactions when added to Mueller-Hinton Broth, making the minimum inhibition concentration difficult to determine. After culturing the highest concentrations of microdilution, Syzygium mimicum was found potentially bactericidal on Staphylococcus saprophyticus at 100% concentration. In conclusion, Syzygium mimicum leaves show antibacterial potential and may be further studied as a natural antibacterial agent.
Undergraduate Thesis: (BS Biology major in Medical Biology) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2